Probing the Effects of Strong Electromagnetic Fields with Charge-Dependent Directed Flow in Pb-Pb Collisions at the LHC - Acharya, S.; Adamovã, D.; Adler, A.; Adolfsson, J.; Aggarwal, M.M.; Aglieri Rinella, G.A.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Akindinov, A.; et al. (American Physical Society, 2020)
The first measurement at the LHC of charge-dependent directed flow (v₁) relative to the spectator plane is presented for Pb-Pb collisions at √ˢɴɴ = 5.02 TeV. Results are reported for charged hadrons and D⁰ mesons for the transverse momentum intervals Pᴛ > 0.2 GeV=c and 3 < Pᴛ < 6 GeV=c in the 5%–40% and 10%–40% centrality classes, respectively. The difference between the positively and negatively charged hadron v₁ has a positive slope as a function of pseudorapidity η, dΔv₁=dη = [1.68 ± 0.49(stat) ± 0.41(syst)] × 10⁻⁴. The same measurement for D⁰ and D̄⁰ mesons yields a positive value dΔv₁=dη [4.9 ± 1.7(stat) ± 0.6(syst)] × 10⁻¹, which is about 3 orders of magnitude larger tan the one of the charged hadrons. These measurements can provide new insights into the effects of the strong electromagnetic field and the initial tilt of matter created in noncentral heavy ion collisions on the dynamics of light (u, d, and s) and heavy (c) quarks. The large difference between the observed Δv₁ of charged hadrons and D⁰ mesons may reflect different sensitivity of the charm and light quarks to the early time dynamics of a heavy ion collision. These observations challenge some recent theoretical calculations, which predicted a negative and an order of magnitude smaller value of dΔv₁=dη for both light flavor and charmed hadrons.
Keywords: Physics; Hadron; Pseudorapidity; Particle physics; Meson; Charge (physics); Charged particle; Ion; Quantum mechanics; https://purl.org/pe-repo/ocde/ford#1.03.03